The Relationship Between Pa Lecturers' Caring Code And Students' Learning Motivation In The Level Iii Nursing Study Program, Santa Elisabeth College Of Health Sciences, Medan - Karo, Mestiana Br; Saragih, Ice Septriani; Zebua, Erliana (Universitas Aisyah Pringsewu, 2025)
Learning motivation is essential in the learning process, as it contributes to the achievement of educational objectives. One strategy to enhance students’ learning motivation is the implementation of the academic advisor (PA) lecturer’s caring code. This study aimed to analyze the relationship between the PA lecturer’s caring code and students’ learning motivation in the Level III Nursing Study Program at Santa Elisabeth Health Sciences College, Medan. This study employed a quantitative research design with a cross-sectional correlational approach. The population and sample consisted of 97 students selected using a total sampling technique. Data were collected using a structured questionnaire and analyzed using the Spearman rank correlation test. The results indicated that the PA lecturer’s caring code was predominantly categorized as good, with 65 respondents (67%). Most students demonstrated high learning motivation, with 78 respondents (80.4%). Statistical analysis revealed a significant relationship between the PA lecturer’s caring code and students’ learning motivation (p = 0.001; p 0.05), with a correlation coefficient (?) of 0.338. This finding indicates a weak but positive and unidirectional relationship, suggesting that an increase in the PA lecturer’s caring code is associated with an increase in students’ learning motivation, and vice versa. The findings suggest that maintaining and strengthening the PA lecturer’s caring code may contribute to sustaining and enhancing students’ learning motivation.